2007
DOI: 10.1088/0022-3727/40/12/034
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the thickness of TiO2seeding layer on structural and electrical properties of Bi3.15Nd0.85Ti3O12thin films

et al.

Abstract: Thin films of Bi3.15Nd0.85Ti3O12(BNT) and BNT with various TiO2 seeding layer thicknesses BNT-Tx (x = 10, 20, 30 nm) were fabricated on Pt/Ti/SiO2/Si substrates by the sol–gel method. The influence of the TiO2 seeding layer thickness on the structural and the electrical properties of BNT thin films was investigated. The x-ray diffraction pattern indicated that the BNT thin film with a TiO2 seeding layer showed a-axis preference orientation. The Pr value was a maximum for the BNT-T20 film and decreased with bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…To simplify the discussion, only the (0 0 6) peak, the (2 0 0) peak and the (117) peak are taken into consideration. The degree of c-axis orientation of a BNT thin film a c is roughly estimated as [14,19] a c ¼ Ið0 0 6Þ=½Ið0 0 6Þ þ Ið1 1 7Þ þ Ið2 0 0Þ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To simplify the discussion, only the (0 0 6) peak, the (2 0 0) peak and the (117) peak are taken into consideration. The degree of c-axis orientation of a BNT thin film a c is roughly estimated as [14,19] a c ¼ Ið0 0 6Þ=½Ið0 0 6Þ þ Ið1 1 7Þ þ Ið2 0 0Þ.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [13] considered enhanced a-axis-oriented crystal growth occurred when the crystallization was performed on every spin-coated layer with sufficiently thin thickness. By introducing a TiO 2 seeding layer with the thickness of 20 nm, Li et al [14] obtained a BNT thin film with a high degree of a-axis preference orientation.…”
Section: Introductionmentioning
confidence: 99%
“…According to Aoki's research, a thin TiO 2 layer would lower the crystallization temperature of the PZT thin films on Pt/Ti/SiO 2 /Si substrates . Li's research indicated that TiO 2 seed layer could change the orientation of Bi 3.15 Nd 0.85 Ti 3 O 12 to a ‐axis preference orientation . In this paper, the NKBT thin films with the TiO 2 alternative layer, either on one side, i.e., at the interface between the NKBT and substrate, or on both sides, i.e., at the interface and on the top of the NKBT, were fabricated on Pt/Ti/SiO 2 /Si substrates by the aqueous sol‐gel method.…”
Section: Introductionmentioning
confidence: 84%
“…The rod-like grains increase and plate-like grains decrease in the BIT films after substitution of La 3+ or V 5+ , and also the size of plate-like grains decreases. For BIT based films, the rod-like grains are related to the growth of random orientation and the plate-like grains are related to the growth of c-axis orientation Li et al,2007). In Fig.…”
Section: The Effect Of La/v Substitutionmentioning
confidence: 99%